2021
DOI: 10.3389/fnhum.2021.679191
|View full text |Cite
|
Sign up to set email alerts
|

Advantage of Handwriting Over Typing on Learning Words: Evidence From an N400 Event-Related Potential Index

Abstract: The growing implementation of digital education comes with an increased need to understand the impact of digital tools on learning. Previous behavioral studies have shown that handwriting on paper is more effective for learning than typing on a keyboard. However, the impact of writing with a digital pen on a tablet remains to be clarified. In the present study, we compared learning by handwriting with an ink pen on paper, handwriting with a digital pen on a tablet, and typing on a keyboard. Behavioral and elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In terms of the empirical evidence, numerous studies in neuroscience, experimental psychology, and writing have found differences in learning and performance in the two writing environments. Thus, various studies have found the advantage of pen-and-paper writing over computer writing in improving spelling (Cunningham & Stanovich, 1990) as well as letter and word learning (Ihara et al, 2021;Longcamp et al, 2006). In addition, a recent study by Askvik et al (2020) showed that, as compared to typing, handwriting was associated with increased activation in the brain areas important for memory and learning.…”
Section: Pen-and-paper Versus Computer-based Writingmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the empirical evidence, numerous studies in neuroscience, experimental psychology, and writing have found differences in learning and performance in the two writing environments. Thus, various studies have found the advantage of pen-and-paper writing over computer writing in improving spelling (Cunningham & Stanovich, 1990) as well as letter and word learning (Ihara et al, 2021;Longcamp et al, 2006). In addition, a recent study by Askvik et al (2020) showed that, as compared to typing, handwriting was associated with increased activation in the brain areas important for memory and learning.…”
Section: Pen-and-paper Versus Computer-based Writingmentioning
confidence: 99%
“…The effects of environment in writing can be justified from multiple theoretical perspectives, (e.g., Hayes, 2012;Kress, 2003;Mangen & Velay, 2010), and findings from neuroscience (Askvik et al, 2020;Ihara et al, 2021) and writing research (Chan et al, 2017) have shown that the nature of learning and performance can differ depending on whether paper or computer is involved. Surprisingly, however, except for the research on testing (Barkaoui & Knouzi, 2018), the performance environment has been practically ignored in second language acquisition (SLA) research.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence on the variations in the mental processes and learning outcomes in different writing modalities also comes from neuroscientific approaches using electroencephalography (EEG; Ihara et al 2021) and functional magnetic resonance imaging (fMRI; Vinci-Booher and James 2020). Embodied theories also constitute a common theoretical framework in this line of research (e.g., Askvik et al 2020).…”
Section: Theoretical Framingmentioning
confidence: 99%
“…A recent EEG study by Askvik et al (2020) reported that, as compared to typing, handwriting with digital pen was associated with increased activation in the brain areas important for memory and for encoding of new information. Using the EEG technique, Ihara et al (2021) has found increased word learning by means of handwriting (with either ink or digital pen) as compared to word learning using typing. Additionally, the participants reported more positive mood in the handwriting condition as compared to typing.…”
Section: Theoretical Framingmentioning
confidence: 99%
See 1 more Smart Citation